Epidemiology and risk factors of Helicobacter pylori infection in Timergara city of Pakistan: A cross-sectional study - Syed Rafiq Hussain Shah; Babiker Saad Almugadam; Akbar Hussain; Tauseef Ahmad; Shehzad Ahmed; Shahida Sadiqui (Elsevier, 2021)
Objective: H. pylori infection remains a major public health challenge. Our study aimed to determine the prevalence of H. pylori infection among the local population of the Timergara city in Lower Dir District of Pakistan and investigating the common risk factors associated with disease development. Methods: Between September 2016 to January 2017, 520 individuals have involved in this study. A venous blood sample along with questionnaire data was collected from each participant and H. pylori infection investigated using Indirect Enzyme-Linked ImmunoSorbent Assay. Results: Out of 520 persons studied, 115 (22.1%) were positive and 405 (77.9%) were negative. The majority of infected individuals were males 79 (29.4%) compared to females 34 (14.3%), P value˂0.000. The probability of H. pylori infection was more among smokers 32 (33%), snuff addictive 29 (35.8%), and regular soft drinks takers 57 (43.5%). Furthermore, the logistic regression revealed that the odds of developing H. pylori infection were significantly higher in males (AOR:2.1, 95%CI:1.0-4.7), smokers (AOR:1.7, 95%CI:0.4-2.1), snuff addiction (AOR:5.5, 95%CI:1.2-24.1), no regular toothpaste users (AOR:16.1, 95%CI:8.7-29.8), and regularly soft drinks takers (AOR:4.5, 95%CI:1.7-12.0). Likewise, it was greater in no formal (AOR:3.3, 95%CI:3.7-2.9), primary school (AOR:1.7,95%CI:0.0-0.0), and secondary school (AOR:5.5,95%:2.3-13.2) educated persons compared to individuals of University education level. Conclusions: Our study has highlighted the epidemiology and risk factors associated with H. pylori infection in Timergara city and revealed the need for further studies to a better understanding of the epidemiology of H. pylori infection, which is helpful in diagnosis and prevention of disease.